Strategi Bertahan Petani Jagung Menghadapi Ketidakpastian Harga Jual dan Perubahan Iklim - Helbawanti, Octaviana; Hikmah Widi, Riantin; Rosliyati, Ati; Nuraini, Candra (Pusat Unggulan Riset Pengembangan Lahan Suboptimal (PUR-PLSO) Universitas Sriwijaya, 2024)
Helbawanti, O., Widi, R.H., Rosliyati,A., & Nuraini, C. (2024). Coping strategy of maize farmers in the struggle with the selling price uncertainty and climate change. In: Octaviana H et al. (Eds.), Prosiding Seminar Nasional Lahan Suboptimal ke-12 Tahun 2024, Palembang 21 Oktober 2024. (pp. 477–489). Palembang: Penerbit & Percetakan Universitas Sriwijaya (UNSRI).Maize farmers struggle to purchase production factors and provide for household needs due to low incomes. Middlemen dominantly determine the price of maize harvested by farmers. Limited market access and lack of post-harvest handling results in very low purchase prices by middlemen. Farmers often plant maize rather than rice because it experiences longer droughts than the rainy season. The study was conducted to analyze farmers' attitudes towards the risk of price and climate uncertainty in maize farming. The method used was an analysis of risk sources including human resources, processes, productivity, and reputation. The assessment of price and climate uncertainty used risk mapping. The results explained price uncertainty and drought at high risk level. The impact or severity of the risk of price uncertainty at a large level. The likelihood of price uncertainty was at the high level of very frequent, while drought was at the average level of frequent. The risk sources of price uncertainty and drought affected the purchasing behavior of production factors, which did not increase and tended to decrease, as well as a decrease in post-harvest handling of maize. The purchase of fertilizer and payment of labor costs reduced the profit margin of maize sales, which were subjected to pressure from middlemen who determined the purchase price. The inability to add value to maize weakens the farm household economy as farmers had no other source of income. The farming risk sources of price uncertainty and prolonged drought were sources of risk that need to be controlled.